Hunter Killer - Robinson Patrick : 1963-; Patrick Robinson (London : William Heinemann, 2005)
The terrifying battle for a desert kingdom has begun, as the oil fields explode and the global economy is plunged into chaos. Former Security Advisor to the President, Admiral Arnold Morgan, must lead the offensive to expose the foulest treachery since World War II before America's worst nightmare becomes reality.